2014
DOI: 10.1530/joe-14-0335
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and curcumin enhance pancreatic β-cell function by inhibiting phosphodiesterase activity

Abstract: Resveratrol (RES) and curcumin (CUR) are polyphenols that are found in fruits and turmeric, and possess medicinal properties that are beneficial in various diseases, such as heart disease, cancer, and type 2 diabetes mellitus (T2DM). Results from recent studies have indicated that their therapeutic properties can be attributed to their anti-inflammatory effects. Owing to reports stating that they protect against β-cell dysfunction, we studied their mechanism(s) of action in β-cells. In T2DM, cAMP plays a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 50 publications
4
79
0
1
Order By: Relevance
“…Our results indicated that curcumin and exercise increased the levels of cAMP in Gas (Fig 7A). This result confirms the results of a previous report, which demonstrated the potential of curcumin to increase cAMP levels [34,67]. Identification of cAMP as a target for curcumin in this present study might explain how curcumin mimics some aspects of exercise.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…Our results indicated that curcumin and exercise increased the levels of cAMP in Gas (Fig 7A). This result confirms the results of a previous report, which demonstrated the potential of curcumin to increase cAMP levels [34,67]. Identification of cAMP as a target for curcumin in this present study might explain how curcumin mimics some aspects of exercise.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…While polypharmacy has traditionally required multiple drugs, there is also potential for a single agent to impact multiple pathways. For example, past studies have demonstrated that curcumin may prevent the onset of diabetes (Rouse et al, 2014) and can also impact neuropathy independent of glycemic control (Sharma et al, 2007). Curcumin, while showing some promising therapeutic properties, has distribution and bioavailability issues that restrict its development as a clinically-viable therapy (Hu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the potential interactions of MET and bioactive dietary components with known antitumor activities for CRC prevention and treatment, and specifically in the context of targeting CSC, have not been delineated. The importance of the latter is underscored by recent reports that dietary factors including the soy isoflavone genistein (Gen) (Montales et al 2012;Rahal et al 2013), polyphenolic compounds present in blueberries (Montales et al 2012), curcumin (Kakarala et al 2010), and resveratrol (Kao et al 2009), all of which have been reported to possess anti-metabolic/anti-diabetic properties (Gilbert and Liu 2013;Valsecchi 2013;Yeh et al 2014;Rouse et al 2014), can inhibit expansion of basal stem-like mammary cells with tumorigenic potential.…”
Section: Introductionmentioning
confidence: 99%